Home [compact disc, unabridged] : a novel - Robinson, Marilynne (Macmillan Audio, 2008)
With her father ailing, Glory Boughton has returned home to Gilead to care for him. Shortly after she returns, her brother Jack shows up after a twenty year absence. As the family copes with the death of their patriarch, they learn valuable lessons about love, death, and the fortitude of familial bonds.